Survival in nursery of native species saplings obtained from natural regeneration of forest fragments - Viani, Ricardo Augusto Gorne; Rodrigues, Ricardo Ribeiro (Pesquisa Agropecuaria Brasileira, 2007)
Seedling survival was evaluated regarding transplanted saplings obtained from natural regeneration of a Semideciduous Seasonal Forest fragment, located at Bofete, São Paulo State, Brazil. Shrub and trees species seedlings up to 30 cm height were collected from samples sited on a forest remnant, transplanted to a nursery under 50% shade tissue, and evaluated periodically during nine months. A total of 2,424 seedlings, belonging to 110 species were transferred to the nursery. Average survival reached 69%, although this survival rate was quite variable according to the species, families and height classes of the evaluated individuals. In spite of the fact that pioneer species presented higher survival rate, several non-pioneer species also obtained high values of survival. Besides, many of the survivor species are usually not available in forest nurseries of the São Paulo State. The transference of seedlings from natural regeneration of forest fragments to forest nurseries seems to be a complementary and a viable method in order to produce saplings of native species, increasing diversity within nurseries with forest restoration purposes.